Solubility and mass transfer coefficient of oxygen through gas– and water–lipid interfaces. Issue 3 (13th February 2021) - Roppongi, Takao; Mizuno, Naho; Miyagawa, Yayoi; Kobayashi, Takashi; Nakagawa, Kyuya; Adachi, Shuji
Abstract : Abstract: The solubility of oxygen and its transfer rate to the lipid phase play important roles in lipid oxidation, which affects the taste and safety of lipid‐containing foods. In this study, we measured the Henry's constants (solubility) of oxygen for fatty acids, fatty acid esters, and triacylglycerols (TAGs; vegetable oils), as well as the mass transfer coefficients of oxygen at the gas– and water–lipid interfaces. The constants and coefficients were estimated by analyzing the change over time in the oxygen partial pressure or concentration in the closed container based on the mass balance equations of oxygen in the gas and liquid phases. The constant for water obtained by the method used in this study was in agreement with the previously reported value to confirm the validity of the method. The constants for lipids depended on the lipid type, and were higher in the order of fatty acid ester, fatty acid, and TAG. That is, the solubility of oxygen decreased in this order. For all lipids, the constant increased as the number of carbon atoms in the fatty acid chain increased. The constants for fatty acids and their esters were linearly correlated with the enthalpies of evaporation of the lipids. The mass transfer coefficients of oxygen at the gas–liquid interface were on the order of 10 −5 m/s for water and methyl dodecanoate and of 10 −6 m/s for TAG (rapeseed oil). The coefficient at the water–lipid interface was on the order of 10 −6 m/s. Practical Application: The Henry's constants (solubility) and transfer rate of oxygen to the lipid phase, fatty acids, fatty acid esters, and triacylglycerols (TAG) were measured. The lipids solubilized three to five times more oxygen than water, and mass transfer rate of oxygen at gas– and water–lipid interfaces were almost same. The constants for fatty acids and fatty acid esters were linearly correlated to their enthalpies of evaporation, and this correlation is expected to be useful for estimating the Henry's constants for other fatty acids and their esters.